Culture also eats innovation for breakfast!. Issue 12 (18th October 2019) - Oliver, John J.
Abstract : Purpose: This paper examines the role that corporate culture plays in shaping firm performance. It specifically examines how a corporate crisis event resulted in adaptive cultural responses that may be inhibiting the level of firm innovation. Design/methodology/approach: The research presents a longitudinal analysis of risk and innovation words contained in Barclays Plc corporate annual reports. Findings: In the wake of corporate fraud and punitive charges, Barclays Plc introduced a number of new governance structures and a new code of conduct for employees. These initiatives moved the firm away from excessive risk taking, but may have also placed an emphasis on risk aversion at the expense of innovation. Practical implications: The insight provided by this viewpoint and analysis may help CEOs and their management teams to better understand how changes in strategy, and or new corporate initiatives, create adaptive changes in culture. These changes, whilst making improvements in one area, may detract from performance in other parts of the firm. Originality/value: This paper provides a highly original look at corporate culture and has employed an innovative methodology to underpin the analysis and subsequent viewpoint.